PENGEMBANGAN KAWASAN PESISIR DENGAN MEMANFAATKAN RUANG TERBUKA SEBAGAI TAMAN REKREASI DAN SISTEM PENGELOLAAN JARINGAN PERSAMPAHAN YANG LAYAK PADA RT 8 KELURAHAN MANGGAR BARU - Lhara Sari, Oryza; Putri, Andina Prima; Yanti, Rossana Margaret Kadar; Apriani, Dyah Wahyu (Jurnal Pengabdian Masyarakat Sabangka, 2023)
Manggar Baru is one of the sub-districts in East Balikpapan District, Balikpapan City. According to the 2012-2032 RTRW of Balikpapan City, Manggar Baru is planned to become a minapolitan and tourism area based on the geographical conditions which are located along the coast. Optimizing the potential of coastal areas is carried out by developing existing land or open spaces into proper beach tourism and can be enjoyed by residents and visitors. Based on the results of a survey that has been conducted, Kampung Nelayan RT 8 Kelurahan Manggar Baru has unfavorable solid waste conditions. Overcoming this problem regarding waste regulations, several things can be done, namely managing existing waste conditions through the provision of infrastructure such as garbage dumps in front of every house in RT 8 to make it easier to collect and sort waste. Then, conduct outreach to the surrounding community regarding education on waste management based on its type and utilization. One of the uses of waste that can be developed is to use plastic bottles or other plastic waste to make eco bricks. In addition, the results of the ecobrick that has been made can be used as material to build a vertical garden. The garden area can be used to develop toga plants for the local community. Seeing the waste problems that occur in RT 8, it is necessary to empower the community in managing waste. Community empowerment can be carried out using the Asset-Based Community Development (ABCD) approach which first takes inventory of assets owned by the community to be used as resources in waste management. The community empowerment methods that require participation include Rapid Rural Appraisal (RRA), Participatory Rapid Appraisal (PRA), Participatory Learning and Action (PLA) and Participatory Training. It is hoped that some of the solutions described above can be a way out of existing problems and can have an impact on both the surrounding community and the people who come to use these facilities.